A study to Indicate the Infection Prevalence with the Giardia lamblia and Entameoba histolytica parasites in Al Najaf Governorate for the year 2022 - Abdul-Zahra, Noor I.; Taiban, Zahraa K. (Medical Science Journal for Advance Research, 2024)
Background: study of parasitic infection is considered one of the challenges in maintainable progress. Aim: It is a statement of the prevalence of parasite infection in Najaf Governorate for the year 2022 for some age groups. Methods: Data for the study are collected from the Digestive System Hospital in Al-Najaf Governorate, and they are analyzed, showing the percentages of infections with both parasites, and showing the environment that encourages infection and its causes. Results: There were 622 specimens were collected from gastrointestinal patients who suffer from similar symptoms to some extent, which the parasitic infections were E.histolytica, and G.lamblia, found to be 620 (93.65%) with E.histolytica infection and 42 (6.34%) with G.lamblia infection, and the results showed that the highest rate of total infection in the age group from 15-45 years. And the least in age group 10-14 years. According to sex the highest infection were in females as total infections, and the results showed that the highest rate of G. lamblia infection in the age group from 15-45 years. And the least percentage in age more 45 years. And the highest percentage of E. histolytica infection in the age group from 15-45 years. And the least in age group 10-14 years. Conclusion: We conclude from this study that parasite infection especially G. lamblia and E. histolytica include all ages, sexes. but the most vulnerable age groups are in terms of bodily building and defensive immunity of the body.